2017
DOI: 10.1186/s40691-017-0093-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived ease of use and usefulness of sustainability labels on apparel products: application of the technology acceptance model

Abstract: This study explores consumers’ perceptions of sustainability labels on apparel products and examines sustainability labels as an effective means of determining consumers’ purchase intentions, using the technology acceptance model (TAM) as the foundation. Data were collected via self-administered web-based surveys from 903 randomly selected shoppers throughout the United States (U.S.). Findings validated that perceived ease of use, perceived usefulness, attitudes, and purchase intention were associated with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 48 publications
2
58
0
17
Order By: Relevance
“…believed that this set of elements was useful for them and for everyone else. In this sense, this finding was consistent with Ma et al [82], according to whom the usefulness generated by the adoption of sustainable practices produces positive impacts that spill over into the environmental dimension as well as the social and economic sphere.…”
Section: Discussionsupporting
confidence: 91%
“…believed that this set of elements was useful for them and for everyone else. In this sense, this finding was consistent with Ma et al [82], according to whom the usefulness generated by the adoption of sustainable practices produces positive impacts that spill over into the environmental dimension as well as the social and economic sphere.…”
Section: Discussionsupporting
confidence: 91%
“…Several scholars claimed that providing a technology-based solution increases awareness and understanding of electricity consumption [23,30,[54][55][56]. As such, [22] confirmed that after the installation of real-time aggregate feedback in college dormitories, a 55% reduction of electricity consumption was evident.…”
Section: Powerpediamentioning
confidence: 77%
“…Kim et al 2009;Kim dan Forsythe, 2008). Ma et al (2017) mengungkapkan bahwa kemudahan penggunaan (perceived ease of use) dan kegunaan (perceived usefulness) berkontribusi pada pembentukan sikap pengguna dalam menggunakan teknologi yang pada akhirnya berdampak pada meningkatnya niat pengguna untuk menggunakan suatu teknologi. Selain itu, perceived ease of use juga disebut memiliki pengaruh positif terhadap persepsi individu terkait dengan kegunaan dalam menggunakan teknologi (perceived usefulness) (Ma et al 2017).…”
Section: Perceived Usefulenessunclassified
“…Ma et al 2017). Dewasa ini, TAM telah diterapkan secara luas untuk menjelaskan penggunaan teknologi oleh konsumen dalam konteks belanja online (Cho dan Wang, 2010; model yang dibangun dapat menjelaskan informasi empiris mengenai data yang dikumpulkan.…”
unclassified